Individuals’ strategies for wellbeing during the integration process: an empirical study of capabilities and opportunities through the eyes of Syrian refugees in the Canton of Vaud, in Switzerland - Widmer, Irina Alexandra (My University, 2020)
Integration concerns everyone in society as a constantly on-going process of constructing belonging and participation as a member of the group. The common objective of the process for individuals is to increase their subjective wellbeing, according to their individual values. However, refugees undergo an extreme case of integration, with all aspects of their life being impacted at once. Therefore, to gain more knowledge about the integration process from the perspectives of individuals, nine qualitative narrative interviews were conducted with adult Syrian refugees living in Canton of Vaud, in Switzerland. This thesis then mobilises the theoretical perspective of the capability approach for conducting a thematic comparison at an interpersonal level. The analysis revealed a common pattern among all interviewees which builds up into a 5-stages integration model–launched by a disruptive event creating a sense of loss and progressing towards (re)building stability and being at peace with one’s new situation–experienced by all interviewees in the same chronological order. Nevertheless, the personal capabilities and opportunities vary, resulting in the adoption of different strategies to deal with the same context and similar objectives at a specific stage.
Mémoire de master : Université de Neuchâtel, 2020
Keywords: wellbeing; integration; refugee; capability approach; strategies/ Bien-être; intégration; réfugié-e-s; capabilités; stratégies